Supporting Creativity and Imagination in the Early Years / Second Edition - Duffy, Bernadette (Open University Press, 2010)
This book considers creativity and imagination in the light of contemporary initiatives such as Every Child Matters, Bird to Three Matters, Sure Start and the Foundation Stage curriculum. Acknowledgements, Introduction, What are Creativity and Imagination and Why are They Important?, The Importance of Creativity and Imagination, Defining Creativity and Imagination, The Creative Process, How Do Creativity and Imagination Develop?, Child Developments and Creativity and Imagination from Birth to 6 Years, Creativity Across the Curriculum, The Contribution of the Arts to Learning, The Development of the Visual and Performing Arts, Theory into Practice, The Role of the Adult, The Organization of Space and Time and Social Contexts, Extending the Race of Experiences, Planning and Implementing and Observing and Recording and Assessing, Conclusion, Bibliography, Index.